Chemical Ablation for Treating Anal Fistulas without Surgical Intervention: Long-Term Results - KARA, BURAK; TÜNEY, DAVUT; YEGEN, ŞEVKET CUMHUR; UPRAK, TEVFİK KIVILCIM (SAGE PUBLICATIONS INC, 2021)
Purposes. This study aimed to evaluate long-term outcomes after the application of a corrosive chemical agent for ablation of epithelial tissue as a non-surgical treatment of anal fistulas. Methods. Adult patients with symptomatic perianal fistula were prospectively included in the study. The fistula tract was irrigated with a 5% silver nitrate solution. The primary outcome measured in this study was the rate of clinical healing after long-term follow-up. Factors that may affect healing were also analysed. Results. A total of 186 patients with anal fistula were analysed. After irrigation with silver nitrate, 82 (44%) patients had complete clinical healing during a median follow-up time of 50 (7-64) months. Patients with intermittent discharge had a significantly higher rate of complete clinical healing than those with continuous discharge (P < .04). Fistulas without abscesses or secondary tracts had a significantly higher rate of complete clinical healing than the other types (P = .007). Conclusion. Chemical ablation of the epithelium of the anal fistula yields promising long-term outcomes in the management of anal fistulas without surgical intervention.
Keywords: anal fistula; chemical ablation; long term